Alterations of the gut microbiota and metabolites by ShenZhu TiaoPi granule alleviates hyperglycemia in GK rats - Zhao, Jindong; Fang, Zhaohui (Frontiers in Microbiology, 2024)
ShenZhu TiaoPi granule (STG) is a compound prescription of Chinese medicine applied for the treatment of type 2 diabetes mellitus (T2DM). Previous studies have indicated a hypoglycaemic effect, but the underlying mechanism remains unclear. GK rats were used to establish an in vivo T2DM model (Mod). The metformin (Met) and STG treatment time was 12 weeks. Fasting blood glucose (FBG) and insulin levels and the area under the glucose curve (GAUC) were measured. Intestinal pathology and permeability were observed. Microbial diversity and metabolomics were used to investigate the underlying mechanisms. Compared with the Con group, the T2DM Mod group presented significant differences in weight, FBG, GAUC, and HOMA-IR indices (P < 0.01). Met and STG improved these indicators (P < 0.01). The pathological morphology and ZO-1 protein levels in the intestines of the Mod group of rats were altered, leading to increases in the LPS and IL-1β levels. These intestinal conditions improved, and LPS and IL-1β levels were significantly decreased in the Met and STG groups (P < 0.01). Changes in the gut microbiota and metabolites occurred in the model group. In the STG groups, the abundance of Intestinimonas increased, and the abundance of Eubacterium coprostanoligenes decreased significantly (P<0.05). Moreover, STG also regulated 2-deoxyglucose, beta-muricholic acid and dioxolithocholic acid production. In addition, the main metabolic pathways affected by STG were bile acid biosynthesis and cholesterol metabolism. Intestinimonas and D-Maltose_and_Alpha-Lactose may be potential biomarkers for the effects of STG. STG improves hyperglycaemia via the gut microbiota and metabolites in GK rats.